2022
DOI: 10.1002/cctc.202200927
|View full text |Cite
|
Sign up to set email alerts
|

A Homogeneous‐Heterogeneous Kinetic Study of Oxidative Coupling of Methane (OCM) on La2O3/CeO2 Catalyst

Abstract: A La 2 O 3 /CeO 2 catalyst was synthesized and achieved 19 % C 2 + yield with 65 % C 2 + selectivity at 650 °C. The doping of CeO 2 not only enhanced catalytic performance, but also improved catalyst stability in the presence CO 2 and H 2 O. This study investigated the kinetics on La 2 O 3 /CeO 2 over a wide range of operating conditions. Planar laser-induced fluorescence was implemented to directly observe the presence of formaldehyde, as the first time reported in OCM. A packed bed reactor model was construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 64 publications
2
11
0
Order By: Relevance
“…However, because the resulting hydrocarbons can be easily activated compared to CH 4 due to their weaker C-H bond strength, their overoxidation to CO x is a challenge, which results in a loss of selectivity and the resulting yield at high CH 4 conversion. [8][9][10] Various catalysts, such as Li/MgO-, La 2 O 3 -, and Sm 2 O 3 -based catalysts, were investigated to improve the process's selectivity and reaction rate, [11][12][13][14][15] One of the most studied catalysts is alkali metal-based tungstate, such as Na 2 WO 4 , due to its high C 2 selectivity. The unique feature of the tungstate catalysts is that the addition of H 2 O in the reactant stream improves the CH 4 conversion rate and the selectivity to C 2 products.…”
Section: Introductionmentioning
confidence: 99%
“…However, because the resulting hydrocarbons can be easily activated compared to CH 4 due to their weaker C-H bond strength, their overoxidation to CO x is a challenge, which results in a loss of selectivity and the resulting yield at high CH 4 conversion. [8][9][10] Various catalysts, such as Li/MgO-, La 2 O 3 -, and Sm 2 O 3 -based catalysts, were investigated to improve the process's selectivity and reaction rate, [11][12][13][14][15] One of the most studied catalysts is alkali metal-based tungstate, such as Na 2 WO 4 , due to its high C 2 selectivity. The unique feature of the tungstate catalysts is that the addition of H 2 O in the reactant stream improves the CH 4 conversion rate and the selectivity to C 2 products.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Karakaya et al utilized the same reaction network to explore the kinetic behavior under non-isothermal conditions, which captured the significant temperature rise within the catalyst bed associated with the high exothermicity of OCM under low pressure. , Recently, various reported gas-phase mechanisms were compared to better describe the gas-phase experiments in the presence of CH 4 and O 2 to utilize in the OCM microkinetic study . The findings in the gas-phase mechanism were introduced in the microkinetic study on the La 2 O 3 –CeO 2 catalyst with a reported surface mechanism under low pressure (total 101 kPa) …”
Section: Introductionmentioning
confidence: 99%
“…The La 2 O 3 –CeO 2 catalyst was also found to be coke-tolerant, which is beneficial for industrial application. The doping of CeO 2 into La 2 O 3 can improve the catalytic performance as well as the stability in the presence of CO 2 and H 2 O …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations